Impact of MRI-Based Tumor Margin Assessment on Reducing Positive Margins in Breast-Conserving Surgery - Khalid Shakeel Babar, Fazal Hussain, Sasui Memon, Samreen Mushtaq, Muhammad Usman, Tahir Baig (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Breast-conserving surgery (BCS) is an established treatment for early-stage breast cancer. Achieving negative surgical margins is essential to minimize local recurrence and avoid re-excision procedures. However, positive margins remain a common challenge in breast-conserving surgery. Magnetic resonance imaging (MRI) provides high sensitivity in detecting tumor extent, multifocal disease, and occult lesions, which may improve surgical planning. Objective: To evaluate the impact of preoperative MRI-based tumor margin assessment on the rate of positive surgical margins in patients undergoing breast-conserving surgery. Methods: A retrospective observational study was conducted at a tertiary care teaching hospital between January 2023 and August 2023. Medical records of women with early-stage breast cancer who underwent breast-conserving surgery were reviewed. Patients were categorized into two groups according to imaging strategy: conventional imaging (mammography and/or ultrasound) and MRI-assisted evaluation. Demographic characteristics, tumor features, imaging findings, surgical procedures, and histopathological margin status were analyzed. Positive margin rates and re-excision requirements were compared between groups. Results: A total of 168 patients were included. The mean patient age was 49.3 ± 10.2 years. Patients assessed with MRI demonstrated improved preoperative identification of tumor boundaries and multifocal lesions. The rate of positive surgical margins was lower in the MRI group compared with the conventional imaging group. MRI-guided planning also resulted in a lower need for re-excision surgery. Conclusion: Preoperative MRI-based tumor margin assessment can enhance surgical planning and reduce positive margins in breast-conserving surgery. Selective use of MRI in suitable patients may improve oncologic outcomes and reduce repeat surgical procedures. Keywords: Breast-conserving surgery, breast MRI, surgical margins, breast cancer, re-ex